Effect of two-weeks of school-based sprint training on physical fitness, risk factors for cardiometabolic diseases and cognitive function in adolescent girls: A randomized controlled pilot trial - Williams, Ryan A.; Dring, Karah J.; Morris, John G.; Sunderland, Caroline; Nevill, Mary E.; Cooper, Simon B. (Frontiers in Sports and Active Living, 2022)
Background School-based physical activity interventions are accessible to most adolescents and could enhance adolescent cardiometabolic health and cognition; yet the feasibility and success of school-based physical activity interventions is understudied. Methods Sixteen adolescent girls (age: 11.7 ± 0.3 y; height: 1.58 ± 0.07 m; body mass: 45.5 ± 9.2 kg) were randomized to either an intervention (2-weeks sprint training; n = 8) or control group (continuation of regular physical activity levels; n = 8). Following familiarization, all participants completed baseline measurements including fasted and postprandial capillary blood samples, a battery of cognitive function tests (Stroop Test, Sternberg Paradigm and Flanker Task), and an assessment of physical fitness (20 m sprint and multi-stage fitness test). The intervention group completed 2-weeks progressive sprint training (3 sessions per week: week one 6 × 10 s sprints, week two 8 × 10 s sprints). Follow-up measurements were completed 48 h after the final sprint training session. Data were analyzed via ANCOVA to examine between group differences at follow-up whilst controlling for baseline score. Results Accuracy in the intervention group during the three-item Sternberg paradigm was greater when compared with the control group (Intervention: 99.6 ± 1.1%; Control: 97.7 ± 2.2%, p = 0.046). BDNF concentration was also higher in the intervention group at follow-up than control group (Intervention: 39.12 ± 9.88 ng.ml−1; Control: 22.95 ± 9.13 ng.ml−1, p < 0.001). There were no differences at follow-up between the intervention and control group for measures of cardiometabolic health (fasted cytokine concentrations or postprandial glycaemic and insulinaemic responses) or on the Stroop Test or Flanker Task (all p > 0.05). However, the intervention group reported enjoying the sprint training and that they found the sessions valuable. Conclusion Two-weeks sprint interval training in a school-setting enhanced working memory and increased concentrations of BDNF in adolescent girls. The intervention was deemed enjoyable and worthwhile by the adolescent girls and thus the longer-term implementation of such an intervention should be examined.